Not so different after all? An event-related potential study on item and source memory for object-scene pairs in German and Chinese young adults - Weigl, Michael; Shao, Qi; Wang, Enno; Zheng, Zhiwei; Li, Juan; Kray, Jutta; Mecklinger, Axel (Frontiers in Human Neuroscience, 2023)
In recent years, several cross-cultural studies reported that Westerners focus more on central aspects of a scene (e.g., an object) relative to peripheral aspects (e.g., the background), whereas Easterners more evenly allocate attention to central and peripheral aspects. In memory tasks, Easterners exhibit worse recognition for the central object when peripheral aspects are changed, whereas Westerners are less affected by peripheral changes. However, most of these studies rely on hit rates without correcting for response bias, whereas studies accounting for response bias failed to replicate cultural differences in memory tasks. In this event-related potential (ERP) study, we investigated item and source memory for semantically unrelated object-scene pairs in German and Chinese young adults using memory measures corrected for response bias (i.e. the discrimination index Pr). Both groups completed study-test cycles with either item memory tests or source memory tests. In item memory blocks, participants completed an old/new recognition test for the central object. Source memory blocks entailed an associative recognition test for the association between object and background. Item and source memory were better for intact than for recombined pairs. However, as verified with frequentist and Bayesian analyses, this context effect was not modulated by culture. The ERP results revealed an old/new effect for the item memory task in both groups which was again not modulated by culture. Our findings suggest that cultural differences in young adults do not manifest in intentional memory tasks probing memory for object-scene pairs without semantic relations when using biascorrected memory measures.